Purchase Intention Produk Smartphone ditinjau dari Aspek Brand Management - Acai Sudirman; Andy Wijaya; Sherly Sherly; Fitria Halim; Anju Bhernadetha Nainggolan (Research Center and Case Clearing House PPM School of Management, 2021)
Online shopping behavior and online learning using electronic devices, such as smartphones, are currently an interesting phenomenon in Indonesia. The use of smartphones which continues to increase sharply is certainly inseparable from the role of the brand management of the smartphone product. This study aimed to analyze the role of brand experience, brand awareness, brand visibility, and brand reputation in improving purchase intention in generation Z. This study used a research design with a quantitative approach. The data were collected through documentation and online questionnaires. This study used a sample of 180 respondents with the determination of the sample size using purposive sampling formula. Partial least squares were applied to examine the relationship between purchase intention, brand experience, brand awareness, brand visibility, and brand reputation. The results of this study showed that of the four hypotheses developed, one hypothesis was rejected, in which the effect of the brand awareness variable on the purchase intention variable did not have a significant effect. Meanwhile, brand experience, brand visibility, and brand reputation had a significant effect on purchase intention. Based on the findings of this study, it is expected that it can provide additional information for various parties such as traditional stores and online stores, also companies that provide smartphone products to consider the factors that encourage consumer purchase intention so that they gain comfort and trust in these products